ChemInform Abstract: Mild Palladium‐Catalyzed Oxidative Direct ortho‐C—H Acylation of Anilides under Aqueous Conditions. Issue 32 (18th July 2013) - Szabo, Fruzsina; Daru, Janos; Simko, Daniel; Nagy, Tibor Zs.; Stirling, Andras; Novak, Zoltan
Abstract The rate accelerating effect of long chain anionic detergent and trifluoroacetic acid under aqueous conditions is shown.